STUDENTS' TOLERANCE ATTITUDE IN RESPONDING TO RELIGIOUS AND CULTURAL DIFFERENCES - Annisa Ritonga, Rayhan Aulia; Saleh, Syarbaini (FORUM PAEDAGOGIK, 2024)
This research examines the tolerance shown by teenagers towards religious and cultural differences in the city of Pematang Siantar. In social relations, understanding tolerance is an important key to creating harmonious relationships between individuals from different backgrounds. This research uses a qualitative approach with descriptive methods. This research method is observation, interviews, and documentation. This research aims to examine and explore more deeply the tolerance attitudes that teenagers must adopt in responding to religious and cultural differences that exist in the city of Pematang Siantar. The results of this research show that teenagers in Pematang Siantar have a positive attitude of tolerance towards religious and cultural differences with indications of awareness of the importance of social harmony. However, several challenges must be overcome, such as the lack of deep understanding among teenagers regarding pluralism and the existence of differences of opinion that are still developing among teenagers. So it is hoped that this research can provide more effective insight to increase the tolerant attitude of teenagers, especially in responding to existing religious and cultural differences.